2022
DOI: 10.1111/and.14503
|View full text |Cite
|
Sign up to set email alerts
|

Micro RNA 200a contributes to the smooth muscle cells growth in aged‐related erectile dysfunction via regulating Rho/ ROCK pathway

Abstract: Aged-related erectile dysfunction (A-ED) is generally regarded as degeneration of penile erectile tissue due to age, male hormone deficiency and concomitant cardiovascular disease. Current pathological studies of A-ED are still limited. In this study, aged rats were divided into AE group (aged rats with ED) and YN group (young normal rats) for evaluating the roles of miRNA-200a and RhoA/ROCK signalling pathway in A-ED. Apo-morphine test, ICP measurement and pathological results were compared between these two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The RhoA/ROCK pathway is highly associated with CSMC functions, and protein kinase A inhibitor (PKI)/RhoA/ROCK signal transduction has been reported in endothelial cells. [ 25,26 ] To explore the downstream signals of MT‐EVs and the association of miR‐10a‐3p/PKIA and RhoA/ROCK signaling axis in CSMC, we evaluated the changes in the RhoA/ROCK pathway, in the four groups. The results revealed that the RhoA/ROCK pathway was activated by PDGF‐BB but could be significantly attenuated by MT‐EVs in CSMC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RhoA/ROCK pathway is highly associated with CSMC functions, and protein kinase A inhibitor (PKI)/RhoA/ROCK signal transduction has been reported in endothelial cells. [ 25,26 ] To explore the downstream signals of MT‐EVs and the association of miR‐10a‐3p/PKIA and RhoA/ROCK signaling axis in CSMC, we evaluated the changes in the RhoA/ROCK pathway, in the four groups. The results revealed that the RhoA/ROCK pathway was activated by PDGF‐BB but could be significantly attenuated by MT‐EVs in CSMC.…”
Section: Resultsmentioning
confidence: 99%
“…[ 45 ] KEGG analysis of miRNA sequencing in sEVs implies that upregulation of miR‐10a‐3p in MT‐EVs may be involved in the RhoA/ROCK pathway, whose signal inactivation induces smooth muscle relaxation and alleviates ED. [ 25,46 ] Interestingly, it was reported that the PKI/RhoA/ROCK signal transduction pathway existed in endothelial cells. [ 26 ] We then explored whether PKIA suppression, mediated by miR‐10a‐3p, induced the RhoA/ROCK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The increased activity of ROCK mediates excessive contraction of VSMCs, inflammatory cell recruitment, endothelial dysfunction, and vascular remodeling [ 10 ]. ROCK has been proven to participate in VSMC proliferation, migration and phenotypic switching [ 12 ]. ROCK can stimulate VSMC proliferation by inducting ERK, cyclin D1 and PCNA [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 5 genes belonging to both groups of genes: APC, KRAS, ROCK2, FGF5, and ITGA5. Among these genes, ROCK2 has been widely studied in arteriosclerosis and vascular smooth muscle cells [10][11][12], indicating that in ASO, ROCK2 may be involved in the microRNA-30a-3p functional process and may be a microRNA-30a-3p direct target gene.…”
Section: Microrna-30a-3p Directly Targets Rock2mentioning
confidence: 99%
“…Male erectile dysfunction (ED) is notably prevalent in patients diagnosed with cardiovascular diseases (CVD). Both conditions share common risk factors and pathophysiological connections, such as endothelial dysfunction, which is commonly attributed to the age-related degeneration of penile erectile tissue or deficiency in male hormonal levels ( 1 , 2 ). In fact, ED has been shown to be an early independent factor of future CVD events ( 3 , 4 ), which suggests an important pathway to initiate preventive measures.…”
Section: Introductionmentioning
confidence: 99%